Implementation of The Domino Card Media Game to Improve Cognition In Understanding the Concept of Numbers - Muklis Riyanto; Meilida Eka Sari; Nadia Hapipa; Tapsina Tapsina (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The aim of this research is to describe how the implementation of the domino card media game is to improve children's cognitive skills in recognizing the concept of numbers and what factors hinder the implementation of the domino card media game to improve children's cognitive skills in recognizing the concept of numbers at Uswatun Hasanah Kindergarten in Sidorejo Village, Lubuklinggau District. West I Lubuklinggau City, South Sumatra Province. The method used in this research is descriptive qualitative, the data collection techniques used are documentation, interviews and observation and the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that these domino cards attract children's attention more than conventional media so that children become focused on learning, and make it very easy for children to introduce the concept of numbers so that the application of the domino card game can improve children's cognitive understanding of the concept of numbers because by using children's domino cards children are more interested and understand better when taught about the concept of numbers. Meanwhile, the supporting and inhibiting factors, namely the domino card media, make it easier for teachers to teach. Interaction between students is more prominent so that students support each other in their learning related to understanding the concept of number symbols. Furthermore, the obstacle was because explaining how to use domino cards was a bit complicated, and made the situation chaotic because the children were fighting over the cards even though the cards had already been given to each of them.